The Influence of Social Media Marketing on Brand Engagement and Consumer Brand Knowledge in Fashion Shoe Products - Fiqh Nurhidayatullah; Muhamad Rendi (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
The digital era has made social media a strategic platform for the fashion footwear industry in building brand engagement and consumer knowledge, but its effectiveness still shows inconsistent results. This study aims to examine the influence of five social media marketing elements including entertainment, customization, interaction, electronic word-of-mouth, and trendiness on brand awareness and brand image of fashion footwear products. A quantitative approach was used with a survey method on 116 respondents selected using purposive sampling from active social media users who have interacted with fashion footwear brands. Data were collected through an online questionnaire based on a four-point Likert scale and analyzed using Structural Equation Modeling with the Partial Least Squares approach through SmartPLS. The results showed that none of the social media marketing elements had a significant effect on brand awareness (R2 = 0.278 in the moderate category), and brand awareness also had no significant effect on brand image (R2 = 0.042 in the weak category). In conclusion, individual brands' social media marketing efforts have a marginal impact on building brand knowledge of fashion footwear products, so integration with a more comprehensive offline marketing strategy is needed, emphasizing content relevance and value propositions, and focusing on the credibility and consistency of brand communication.